Front Cover: Aerobic Aliphatic Hydroxylation Reactions by Copper Complexes: A Simple Clip‐and‐Cleave Concept (Chem. Eur. J. 58/2018). Issue 58 (4th September 2018) - Becker, Jonathan; Zhyhadlo, Yevheniia Y.; Butova, Ekaterina D.; Fokin, Andrey A.; Schreiner, Peter R.; Förster, Moritz; Holthausen, Max C.; Specht, Pascal; Schindler, Siegfried
Abstract : A convenient imine clip‐and‐cleave concept has been developed for the selective hydroxylation of non‐activated C−H bonds of aliphatic aldehydes. Reaction of aldehydes with N, N ‐diethyl‐ethylenediamine leads to the corresponding imine that binds copper(I) ions as a bidentate donor ligand. After exposure of a solution of this complex to dioxygen followed by acidic cleavage of the product the corresponding β‐hydroxylated aldehyde forms. This concept was successfully applied to the hydroxylation of trimethylacetaldehyde as well as adamantane and diamantane 1‐carbaldehydes. More information can be found in the Full Paper by S. Schindler, A. A. Fokin, M. C. Holthausen et al. onpage 15543 . Graphics by Sebastian Hattig.